Optimizing the function of karang taruna in preventing child marriage in Bakung Village, Ogan Ilir - Sartika, Diana Dewi; Purnama, Dadang Hikmah; Soraida, Safira; Istiqoma, Istiqoma; Syafe'i, Akhmad (Universitas Muhammadiyah Magelang, 2025)
Child marriage remains a social problem in Indonesia, especially in rural areas where the prevalence is high. Minimal socialization and low involvement of local institutions are factors that reinforce the occurrence of this practice. This community service aims to optimize the role of Karang Taruna as an agent of social change in efforts to prevent child marriage in Bakung Village, Ogan Ilir Regency. The implementation method included interactive socialization, participatory training, and evaluation. The results showed a significant increase in participants' understanding of the child marriage issue, with an average score increase of 65% between the pre-test and post-test. This activity successfully fostered collective awareness regarding the social, economic, and health impacts of child marriage, and strengthened the capacity of Karang Taruna as an education and advocacy facilitator at the community level. The active involvement of youth, support from the village government, and a collaborative approach proved effective in building a shared commitment to preventing the practice of child marriage at the grassroots level.